COMPARATIVE OF INTRAARTICULAR INJECTION BETWEEN DEXTROSE PROLOTHERAPY VERSUS TRIAMCINOLONE ACETONIDE IN KNEE OSTEOARTHRITIS - Widodo Mardi Santoso; Andhy Indriyono; Badrul Munir; Alidha Nur Rakhmani; Machlusil Husna (Journal of Pain, Headache and Vertigo, 2020)
Knee osteoarthritis (OA) is one of the most common cartilage degenerative disorders that is a major problem because it causes chronic pain and disability. Therefore the method of treatment and prevention of old age is a big challenge. The results of Dextrose Prolotherapy compared to Triamcinolone therapy research are still varied. Objective:  to  compare  the effectiveness  of  Dextrose  Prolotherapy  and  Triamcinolone Acetonide (TA) in the treatment of moderate knee knee OA.True experimental single blind study, at the Neurology Polyclinic Dr. Saiful Anwar General Hospital Malang for 6 months (July-December 2019). Group I; Dextrose Prolotherapy (15%) intraarticularly injected 3 times every 4 weeks and group II; TA one- time intraarticular injection. The parameters studied were The Western Ontario and McMaster  Universities  Osteoarthritis  Index  (WOMAC)  Score,  Numeric  Rating  Scale (NRS), and Range of Motion (ROM), weeks 0, 4, 8, 12 and 24. Forty samples consisted of; the 20 samples of the Dextrose Prolotherapy group consisted of; male: female = 2 (10%): 18 (90%), age 62.4 + 7.28, BMI 25.6 + 3.69 kg / m2, pain duration 22.35 + 20.10 months, history of physiotherapy 40.27 + 20.79 times. Kellgren–Lawrence osteoarthritis severity grade II; 17 (85%), grade III 3 (15%). TA group; male: female = 5 (25%):15 (75%), age 62.5 + 9.02, BMI 28.4 + 5.01 kg/m2, pain duration 15.95 +  16.55  months,  history  of  physiotherapy  34  +  24.87  times.  Kellgren  –  Lawrence osteoarthritis severity grade II; 18 (90%), grade III; 2 (10%). Comparison of NRS at rest Dextrose Prolotherapy vs TA of week 4 (2.60 vs 1.25), week 8 (1.65 vs 1.40), week 12 (0.8 vs 2.05), week 24 (0.75 vs 3.35). Comparison of NRS during activity Dextrose Prolotherapy vs TA week 4 (4.45 vs 3.35), week 8 (3.25 vs 3.55), week 12 (2.55 vs 4.30), week 24 (2.55 vs 5.80). Comparison of ROM flexion Dextrose Prolotherapy vs TA week 4 (127.05° vs 123.60°), week  8  (130.85°  vs  122.95°),  week  12  (130.85°  vs  122.95°),  week  24  (131.05°  vs 122.10°). Comparison of WOMAC score Dextrose Prolotherapy vs TA week 4 (30.05 vs 22.45), week 8 (22.90 vs 23.95), week 12 (19.30 vs 29.05), week 24 (18.95 vs 35.40). Intraarticular Injection Dextrose Prolotherapy is more effective for the long term based on pain scale NRS, WOMAC score and ROM. Whereas short-term TA is more effective than Dextrose Prolotherapy.